2 Answers | Add Yours
First, we need to shift the term from the right side to the left side, such as:
(x-1)/3 - 2 = 0
Before subtracting the terms, they need to have a common denominator, which is 3:
(x - 1 - 6)/3 = 0
We'll cancel the numerator:
x - 7 = 0
We'll add 7 both sides:
x = 7
The requested value of x is x = 7.
then you should first multiply both sides by 3 to get x-1=6
if x-1=6, add one to both sides to find the value of x, thus getting your answer.
you can use the method above for more than just this question, apply it to other mathematical questions that are like this and it should work.
hope that helped.
We’ve answered 396,379 questions. We can answer yours, too.Ask a question